Macroinvertebrates Reveal Water Quality Differences in Various Agricultural Management - Agung Sih Kurnianto; Rufaidah Nur Baiti; Hari Purnomo (Journal of Tropical Biodiversity and Biotechnology, 2021)
Monitoring benthic communities under different agricultural practices and management could potentially become an important tool to evaluate ecosystem health and stability. Benthic macroinvertebrates have been widely used as water quality bioindicators. This study aims to analyze macroinvertebrates in rice field ecosystems affected by three types of management practices, including conventional, semi-organic, and organic. This study was conducted in Sumberjambe and Kemiri, Jember Regency. Macroinvertebrate samples were collected at three sampling stations for each type of rice field, giving out a total of nine stations. Through Ekman grab, samples were obtained and transferred into a jam jar filled with 70% ethanol using a brush. Six ecological indices were selected to describe the diversity of each station. The Principal Component Analysis (PCA) using PAST3 software provided the sample's preference towards the stations and the higher taxa (Class). We also analyzed the similarity of the macroinvertebrate communities between the sampling stations using the Jaccard Similarity Index (JSI). A total of 11 families and 4 classes of macroinvertebrates are recorded. The Shannon-Wiener index shows high diversity for stations with organic management practices (1.318), while the Evenness index shows the highest value for conventional stations (0.9449). The Jaccard similarity index value reports two stations with semi-organic stations as well as semi-organic and organic stations having the highest similarity (JSI = 76.47%), while the lowest similarity value is characterized for conventional and organic stations (JSI = 13.19%).